Connecting the dots: Views on promoting Bidayuh language learning via e-folktales - Campbell, Yvonne Michelle; Ting, Su Hie; Chuah, Kee-Man (Universiti Malaysia Sarawak, UNIMAS, 2012)
Many attempts have been made to encourage the younger generation of indigenous communities to learn their mother tongue. More often than not, such efforts fail since proficiency in the mother tongue is perceived as irrelevant in offering opportunities for social mobility and career advancement. However, the loss of the language means that the cultural knowledge contained in the words and grammar of the language would not be accessible to individuals from the speech community although the language may not be completely lost from the community at large. The study examined the value of Bidayuh folktales to the young generation of Bidayuh as a means to encourage the use of the language. The specific aspects examined include their familiarity with Bidayuh folktales, the value attached to knowing Bidayuh folktales and the Bidayuh language, and their views on the feasibility of learning the Bidayuh language through the use of folktales in electronic forms (e-Folktales). A survey was conducted among 81 Bidayuh adolescents in two urban and two rural areas in Kuching, Sarawak. The results indicated that the Bidayuh adolescents were not familiar with the traditional folktales. Although they acknowledged the need to learn the Bidayuh language, they attributed minimal significance to the role of the language in the modern era. However, they indicated interest in seeing the preservation of the Bidayuh folktales and language in electronic forms. The findings are discussed in the light of the potential of having an electronic-based learning of the language through Bidayuh folktales.